Erythrodermic Psoriasis Managed with Risankizumab - Abdulmajeed Alajlan; Abdulaziz Madani; Tala Ammar Qadoumi; Alhanouf Aljaloud; Mohammed Alessa (Karger Publishers, 2022)
Erythrodermic psoriasis (EP) is a severe, often refractory, variant of psoriasis. Due to the high morbidity and mortality rate associated with EP and other causes of erythroderma, they are often classified as dermatologic emergencies. EP is usually a therapeutic challenge, where topical and conventional systemic therapies have yielded a less than satisfactory result in several patients. Furthermore, there are a limited number of studies evaluating other therapeutic modalities, such as biologic agents, with no clear treatment guidelines. In this case report, we present a patient who was diagnosed as a case of EP and showed an impressive response to risankizumab.